2. Simplify the expression below.
6n2 - 5n2 + 7n2

6n2 - 5n2 + 7n2 is 8n^2

LLionface|Points 150|

Question

Asked 11/21/2014 7:30:54 PM

Updated 11/22/2014 5:55:15 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

s

Rating

There are no new answers.

What is the solution of the system? Use elimination.
3x – 4y = –24
x + y = –1 **Weegy:** The answer is A. (?4, 3). (More)

Question

Updated 11/15/2014 5:12:39 AM

1 Answer/Comment

Use elimination. The solution for 3x – 4y = –24 , x + y = –1 is x = -4 , y = 3 .

Equation 2 multiplied by 3 , we get :

3x + 3y = -3

Equation 1 minus 3x + 3y = -3

3x - 4y - 3x - 3y = -24 - (-3)

-7y = -21

y = 3

x + 3 = -1

x = -1 - 3

x = -4

Equation 2 multiplied by 3 , we get :

3x + 3y = -3

Equation 1 minus 3x + 3y = -3

3x - 4y - 3x - 3y = -24 - (-3)

-7y = -21

y = 3

x + 3 = -1

x = -1 - 3

x = -4

Added 11/15/2014 5:12:39 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/15/2014 5:24:41 AM], Rated good by andrewpallarca

What is the solution of the system? Use elimination. 3x – 4y = 9 –3x + 2y = 9 **Weegy:** D. (?9, ?9) (More)

Question

Updated 11/15/2014 5:05:27 AM

1 Answer/Comment

The solution for 3x – 4y = 9, –3x + 2y = 9 is x = -9, y = -9 .

Equation 1 and equation 2 ,

3x - 3x - 4y + 2y = 9 + 9

-2y = 18

y = -9

3x - 4(-9) = 9

3x + 36 = 9

3x = -27

x = -9

Equation 1 and equation 2 ,

3x - 3x - 4y + 2y = 9 + 9

-2y = 18

y = -9

3x - 4(-9) = 9

3x + 36 = 9

3x = -27

x = -9

Added 11/15/2014 5:05:27 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/15/2014 5:08:26 AM], Rated good by andrewpallarca

What is the solution of the system? Use a graph.
y = x + 5
y = –5x – 1

Question

Updated 11/15/2014 4:44:06 AM

1 Answer/Comment

The solution for y = x + 5 , y = –5x – 1 is x = -1 , y = 4 .

y - y = x + 5 - (-5x - 1)

0 = x + 5x + 5 + 1

-6 = 6x

x = -1

y = -1 + 5

y = 4 .

y - y = x + 5 - (-5x - 1)

0 = x + 5x + 5 + 1

-6 = 6x

x = -1

y = -1 + 5

y = 4 .

Added 11/15/2014 4:44:06 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/15/2014 5:05:52 AM], Rated good by andrewpallarca

1. Solve the absolute value equation, if possible. If there is no solution, explain why.
| 5x + 13| = -7
**Weegy:**
|5x + 13| = -7;
5x + 13 = -7;
5x = -7 - 13;
5x = -20;
x = -20/5;
x = -4;
-(5x + 13) = -7;
-5x - 13 = -7;
-5x = -7 + 13;
-5x = 6;
x = -6/5
There are NO solutions for the equation |5x + 13| = -7
(More)

Question

Updated 11/22/2014 4:55:42 AM

0 Answers/Comments

5. Solve the inequality. Show your work.
6y – 8 = 10
**Weegy:** 6y - 8 = 10
6y = 18
y = 3 (More)

Question

Updated 11/24/2014 9:24:04 PM

0 Answers/Comments

34,461,374

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 768 [Total 6641] Ratings 16 Comments 608 Invitations 0 Offline

There are no comments.